2
$\begingroup$

For $0<\alpha<n$ and $n\geq 2$ we define the Riesz potential by $$ (I_\alpha f)(x) = \frac{1}{\gamma(\alpha)} \int_{\mathbb{R}^n} \frac{f(y)}{|x-y|^{n-\alpha}}\, dy\, , \quad \text{where} \quad \gamma(\alpha)= \frac{\pi^{\frac{n}{2}}\, 2^\alpha\,\Gamma\left(\frac{\alpha}{2}\right)} {\Gamma\left(\frac{n-\alpha}{2}\right)}\, . $$ The following result is well known and regarded as nearly obvious:

Theorem. If $\alpha,\beta>0$, $\alpha+\beta<n$, then $I_\alpha(I_\beta\varphi)=I_{\alpha+\beta}\varphi$ for $\varphi\in\mathscr S_n$.

Formally \begin{eqnarray*} (I_\alpha I_\beta\varphi)^\wedge(\xi) & = & \left((-\Delta)^{\alpha/2}(-\Delta)^{\beta/2}\varphi)\right)^\wedge(\xi) = (4\pi^2|\xi|^2)^{\alpha/2}(4\pi^2|\xi|^2)^{\beta/2}\hat{\varphi}(\xi)\\ & = & (4\pi^2|\xi|^2)^{\frac{\alpha+\beta}{2}}\hat{\varphi}(\xi) = \Big((-\Delta)^{\frac{\alpha+\beta}{2}}\varphi\Big)^\wedge(\xi) =(I_{\alpha+\beta}\varphi)^\wedge(\xi) \end{eqnarray*} and the result follows by taking the inverse Fourier transform.

Having this argument in mind, Stein on p.118 in his Singular integrals and differentiable properties of functions writes `deduction of this formula offer no difficulties'. But is it really a rigorous proof? The problem is that $I_\alpha\varphi$ is defined as a convolution with the distribution, $I_\alpha\varphi=u_\alpha*\varphi$, where $u_\alpha=\gamma(\alpha)^{-1}|x|^{\alpha-n}$. We know that in that case we can use the formula $(u_\alpha*\varphi)^\wedge=\hat{\varphi}\hat{u}_\alpha$. Unfortunately, for most of the functions $\varphi\in\mathscr S_n$, $u_\alpha*\varphi=I_\alpha\varphi\not\in\mathscr S_n$ so the formula $$ (I_\alpha(I_\beta\varphi))^\wedge=(u_\beta*(u_\alpha*\varphi))^\wedge= (u_\alpha*\varphi)^\wedge \hat{u}_\beta $$ is not properly justified.

My question is: Do you know a reference to a rigorous and detailed proof of the above fact?

I will provide an answer to my question by showing how I prove it rigorously, but, perhaps my argument is overly complicated and I am simply not able to see obvious things. Also, I could not find a rigorous and elementary proof anywhere.

$\endgroup$
  • 2
    $\begingroup$ There are many ways to prove this fact. The most elementary one that I know involves the subordination formula $u_\alpha(x) = (\Gamma(\alpha/2))^{-1} \int_0^\infty t^{\alpha/2-1} g_t(x) dx$ (where $g_t(x) = (4 \pi t)^{-n/2} e^{-|x|^2/(4t)}$ is the Gauss–Weierstrass kernel; this formula follows easily from the gamma integral), together with Fubini and $g_t * g_s = g_{t+s}$. Similar argument is typically used to show that the Fourier transform of $u_\alpha$ is indeed $|\xi|^{-\alpha}$ (without multiplication by a constant). $\endgroup$ – Mateusz Kwaśnicki Mar 22 '18 at 22:38
  • $\begingroup$ @MateuszKwaśnicki A very nice argument. You should post it as an answer. $\endgroup$ – Piotr Hajlasz Mar 27 '18 at 23:38
2
$\begingroup$

This is an extended version of my comment.


Let $g_t$ be the Gauss–Weierstrass kernel, $$ g_t(x) = \frac{1}{(4 \pi t)^{n/2}} \, e^{-|x|^2/(4t)} . $$ If $\alpha \in (0, n)$, we have $$ \begin{aligned} \frac{1}{\Gamma(\tfrac{\alpha}{2})} \int_0^\infty g_t(x) t^{\alpha/2 - 1} dt & = \frac{1}{2^n \pi^{n/2} \Gamma(\tfrac{\alpha}{2})} \int_0^\infty t^{-1 - (n - \alpha)/2} e^{-|x|^2 / (4 t)} dt \\ & = \frac{2^\alpha}{\pi^{n/2} \Gamma(\tfrac{\alpha}{2}) \, |x|^{n - \alpha}} \int_0^\infty s^{-1 + (n - \alpha)/2} e^{-s} ds \\ & = \frac{\Gamma(\tfrac{n - \alpha}{2})}{2^\alpha \pi^{n/2} \Gamma(\tfrac{\alpha}{2}) \, |x|^{n - \alpha}} = \frac{1}{\gamma(\alpha)} \, \frac{1}{|x|^{n - \alpha}} \, ; \end{aligned} \tag{1} $$ here we substituted $s = |x|^2 / (4 t)$ and used the gamma integral. Therefore, if $\alpha, \beta, \alpha + \beta \in (0, n)$, we have \begin{align*} \hspace{5em} & \hspace{-5em} \int_{\mathbb{R}^n} \frac{1}{\gamma(\alpha)} \, \frac{1}{|y|^{n - \alpha}} \times \frac{1}{\gamma(\beta)} \, \frac{1}{|x - y|^{n - \alpha}} \, dy \\ & = \frac{1}{\Gamma(\tfrac{\alpha}{2}) \Gamma(\tfrac{\beta}{2})} \int_0^\infty \int_0^\infty g_{t + s}(x) t^{\alpha/2 - 1} s^{\beta/2 - 1} dt ds \\ & = \frac{1}{\Gamma(\tfrac{\alpha}{2}) \Gamma(\tfrac{\beta}{2})} \int_0^\infty \int_0^u g_u(x) v^{\alpha/2 - 1} (u - v)^{\beta/2 - 1} dv du \\ & = \frac{1}{\Gamma(\tfrac{\alpha}{2}) \Gamma(\tfrac{\beta}{2})} \int_0^\infty \int_0^1 g_u(x) u^{(\alpha + \beta)/2 - 1} r^{\alpha/2 - 1} (1 - r)^{\beta/2 - 1} dr du \\ & = \frac{1}{\Gamma(\tfrac{\alpha + \beta}{2})} \int_0^\infty g_u(x) u^{(\alpha + \beta)/2 - 1} du = \frac{1}{\gamma(\alpha + \beta)} \, \frac{1}{|x|^{n - \alpha - \beta}} \, . \end{align*} Here we used: Fubini, (1) and $g_t * g_s = g_{t + s}$; then substitutions $s = u - t$ and $v = t$; then $v = u r$; then beta integral; finally again (1). Again by Fubini, we conclude that $$ I_\alpha(I_\beta f) = I_{\alpha + \beta} f $$ for all nonnegative functions $f$.

$\endgroup$
1
$\begingroup$

Theorem. If $\alpha,\beta>0$, $\alpha+\beta<n$, then $I_\alpha(I_\beta\varphi)=I_{\alpha+\beta}\varphi$ for $\varphi\in\mathscr S_n$.

Lemma. If $\alpha,\beta>0$, $\alpha+\beta<n$, then there is a constant $C_0=C_0(\alpha,\beta,n)$ such that $$ \int_{\mathbb{R}^n}\frac{dy}{|x-y|^{n-\alpha}|y|^{n-\beta}}= \frac{C_0}{|x|^{n-(\alpha+\beta)}}\, . $$

Proof. First you show that the integral is finite for every $x\neq 0$. By rotational symmetry, the integral on the left hand side depends on $|x|$ only. Denoting its value by $f(|x|)$ a simple change of variables (by scaling) show that $f(|x|)=|x|^{\alpha+\beta-n}f(1)$ and the result follows. $\Box$

Proof of the theorem. The lemma and the Fubini theorem easily implies that $$ I_\alpha(I_\beta\varphi)(x)= \frac{C_0\gamma(\alpha+\beta)}{\gamma(\alpha)\gamma(\beta)} I_{\alpha+\beta}\varphi(x). $$ The only problem is to show that the constant is actually equal $1$.

To prove this it suffices to verify that $I_\alpha(I_\beta\varphi)= I_{\alpha+\beta}\varphi$ for just one non-zero function $\varphi$. To this end let $\varphi\in\mathscr S_n$ be such that $\hat{\varphi}=0$ in a neighborhood of $0$. Then $$ I_\alpha(I_\beta\varphi)= I_\alpha\Big(\Big(\underbrace{(4\pi^2|\xi|^2)^{-\beta/2}\hat{\varphi}}_{\in\mathscr S_n}\Big)^\vee\Big) = \left((4\pi^2|\xi|^2)^{-\alpha/2}(4\pi^2|\xi|^2)^{-\beta/2}\hat{\varphi}\right)^\vee= I_{\alpha+\beta}\varphi. $$ The proof is complete. $\Box$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.